Validity and Reliability Evaluation of An Instrument Measuring Students’ Communication and Collaborative Skills - Nina Irawan; Putri Hasdari; Elisa Oktaviani; Cinta Radila Putri; Adam Fernando; Dios Sarkity; Trisna Amelia (Jurnal Ilmiah Profesi Pendidikan, 2026)
Communication and collaboration are widely recognized as core competencies within the framework of 21st-century skills, requiring systematic assessment to ensure their effective development in educational settings. However, the availability of empirically validated instruments specifically designed to measure these competencies remains limited. This study aimed to evaluate the feasibility and psychometric quality of observation instruments developed to assess students’ communication and collaboration skills. A descriptive research design employing a quantitative approach was implemented, focusing on validity and reliability testing. The communication skills instrument consisted of 11 items, while the collaboration skills instrument comprised 27 items. The instruments were administered to 136 students. Item validity was examined using Pearson’s product moment correlation analysis at a significance level of a = 0.05 (r-table = 0.1672). Reliability testing was conducted using Cronbach’s Alpha to determine internal consistency. The results revealed that all 11 items of the communication skills and 20 items of the collaboration skills instrument were confirmed as valid. The reliability analysis demonstrated high internal consistency, with Cronbach’s Alpha coefficients of 0.913 for the communication instrument and 0.951 for the collaboration instrument, both categorized as very high reliability. These findings indicate that the developed instruments possess strong psychometric properties and are suitable for use in assessing students’ communication and collaboration competencies. The study contributes to the provision of validated observational tools that support objective evaluation practices. Future research is recommended to refine the invalid items and extend validation procedures across diverse educational contexts to enhance generalizability and robustness.